Comparative analysis of epigenetic inhibitors reveals different degrees of interference with transcriptional gene silencing and induction of DNA damage - Nowicka, Anna; Tokarz, Barbara; Zwyrtková, Jana; Dvořák Tomaštíková, Eva; Procházková, Klára; Ercan, Ugur; Finke, Andreas; Rozhon, Wilfried; Poppenberger, Brigitte; Otmar, Miroslav; Niezgodzki, Igor; Krečmerová, Marcela; et al. (The Plant journal, 2020)
Repetitive DNA sequences and some genes are epigenetically repressed by transcriptional gene silencing (TGS). When genetic mutants are not available or problematic to use, TGS can be suppressed by chemical inhibitors. However, informed use of epigenetic inhibitors is partially hampered by the absence of any systematic comparison. In addition, there is emerging evidence that epigenetic inhibitors cause genomic instability, but the nature of this damage and its repair remain unclear. To bridge these gaps, we compared the effects of 5-azacytidine (AC), 2'-deoxy-5-azacytidine (DAC), zebularine and 3-deazaneplanocin A (DZNep) on TGS and DNA damage repair. The most effective inhibitor of TGS was DAC, followed by DZNep, zebularine and AC. We confirmed that all inhibitors induce DNA damage and suggest that this damage is repaired by multiple pathways with a critical role of homologous recombination and of the SMC5/6 complex. A strong positive link between the degree of cytidine analog-induced DNA demethylation and the amount of DNA damage suggests that DNA damage is an integral part of cytidine analog-induced DNA demethylation. This helps us to understand the function of DNA methylation in plants and opens the possibility of using epigenetic inhibitors in biotechnology.
Keywords: epigenetic inhibitors; azacytidin; tandemové repetitivní sekvence; Adenosine; Heterochromatin; Epigenesis, Genetic; cytidine analog; DNA damage; genome stability; decitabin; Decitabine; oprava DNA; Tandem Repeat Sequences; Arabidopsis thaliana; Vicia faba; DNA methylation; Cytidine; DNA Repair; Arabidopsis; Gene Silencing; epigeneze genetická; DNA Methylation; metylace DNA; chromozomální aberace; umlčování genů; Chromosome Aberrations; RNA Interference; Azacitidine; heterochromatin; poškození DNA; DNA Damage; cytidin; RNA interference; adenosin